Smartphone Use, Social Media, and Academic Procrastination in Secondary Education: A Multi Method Approach Investigation with Implications for School-Based Interventions - Abdullah, Haslee Sharil Lim; Amalia, Riza; Indreswari, Henny; Hambali, IM; Aditya, Ronal Surya; Rusnila, Rusnila (citeus, 2026)
Academic procrastination has become a significant challenge in digital learning environments, particularly among adolescents with high smartphone and social media usage. This study examines the relationship between mobile phone use and academic procrastination among 262 high school students in Indonesia using a cross-sectional survey, narrative review, and network analysis. Results show 75.6% of students exhibit medium and 20.2% high procrastination levels, with